Evaluación de una política de sustitución de energías fósiles para reducir las emisiones de carbono - Héctor Bravo Pérez; Juan Carlos Castro Ramírez; Miguel Ángel Gutiérrez Andrade; Elsa Patricia Omaña Pulido (El Trimestre Económico)
Background: The energy reform from 2008 promotes the generation and use of renewable energy. Methods: The aim of this work is to evaluate the effectiveness of an environmental policy which promotes the replacement of fossil fuels with renewable energy through tax policy, using a general equilibrium model. Results: Results show that the efficacy of an environmental policy depends on the elasticity of substitution existing in the economy. Conclusions: It is crucial to invest in research and in the development of technology that promotes technological change and fosters greater use of renewable energy, particularly in the most polluting productive sectors in Mexico. It also shows that it is necessary to accelerate energy transition, using clean energy sources as part of the policies and strategies to mitigate greenhouse gases.